The Comparison of Hearing loss in Otosclerosis Patients in response to Stapedectomy : Hearing loss in Otosclerosis Patients - Rasheed, Kashaf; Badar, Syeda Asfara; Khan, Muhammad Azzam; Khan, Rai Saeed; Shahid, Sara; Aslam, Muhammad Azeem; Asif, Sehar; Sadiq, Jahanzaib; Shanawar, Minahil; Sajjad, Ayesha (Pakistan Journal of Health Sciences, 2023)
Otosclerosis patients with remarkable hearing loss are instructed to undergo stapedectomy. Stapedectomy is surgical removal of otosclerosis-damaged stapes, to improve hearing. Objective: To compare the hearing loss in otosclerosis patients as the result of stapedectomy. Methods: Cross-sectional observational study was conducted to compare hearing loss in patients before and after stapedectomy. Total 25 otosclerosis patients of age 25-45 years, were recruited for study through random sampling technique. Setting was Shaikh Zayed Hospital with duration of 6 months from January 2023 to May 2023. Patients undergoing stapedectomy with co-morbid conditions (vertigo, inflammation at side of operation) were excluded. For data collection of study subjects, well-structured self-constructed data collection form was used. Hearing loss was accessed clinically through pure-tone audiometry (PTA). Data were analyzed statistically through SPSS version 24.0 package. Results: Out of 25 patients, 14 (56.0%) were female, while 11 (44.0%) were male. Majority of them (60.0%) were in age group 25-30 years. Out of 25, patients with hearing loss in pre-operative patients with moderate degree 10 (40.0%), mixed degree were 25(100%) and patients in post-operative with moderate degree 14 (56%) and mixed hearing loss were 24 (96.0%) in number. Conclusions: This study presents the findings that in pre-operative stapedectomy patients there was moderate to severe degree mixed hearing loss at all frequencies. Whereas, in post-operative stapedectomy patients there was mild degree mixed hearing loss at all frequencies. Stapedectomy proved to be effective in substantially reducing hearing loss in otosclerosis patients.